Unjust: the health records of youth with personal/family justice involvement in a large pediatric health system - Samantha Boch; Emre Sezgin; Donna Ruch; Kelly Kelleher; Deena Chisolm; Simon Lin (BMC, 2021)
Abstract Background Mass incarceration has had an undeniable toll on childhood poverty and inequality, however, little is known about the consequences on pediatric health. The purpose of this study was to identify and describe the health of pediatric patients with probable personal or family history involvement with the correctional system. Methods A descriptive study was conducted using electronic health record data of 2.3 million youth (ages 0-21 years) who received care in a large Midwestern hospital-based institution from February 2006-2020. We employed a correctional-related keyword search (e.g. jail, prison, probation, parole) to locate youth with probable personal or family history involvement. Health characteristics were measured as clinician diagnostic codes. Results Two percent of the total pediatric population had a correctional keyword in the medical chart (N = 51,855). This 2% made up 66% of all patients with cannabis-related diagnoses, 52% of all patients with trauma-related diagnoses, 48% of all stress-related diagnoses, 38% of all patients with psychotic disorder diagnoses, and 33% of all suicidal-related disorders within this institution's electronic health record database - among other highly concerning findings. Conclusions We captured an alarming health profile that warrants further investigation and validation methods to better address the gaps in our clinical understanding of youth with personal or family history involvement with the correctional system. We can do better in identifying, and supporting families affected by the correctional system.